The Effect of Stock Prices and Exchange Rates on Economic Growth in Indonesia - Saidi, Ld Ode; Adam, Pasrun; Rostin, Rostin; Saenong, Zainuddin; Balaka, Muh. Yani; Gamsir, Gamsir; Asmuddin, Asmuddin; Salwiah, Salwiah (International Journal of Economics and Financial Issues, 2017)
This research aims to investigate the effect of stock prices and exchange rates on Indonesia economic growth. The data were used the quarterly time series spanning in the period, 2004Q1-2015Q3. Econometric model were used to analyze these data is the autoregressive distributed lag (ADL) model. The result of stationary test showed that all of the time series of share prices, exchange rates, and economic growth are stationary at the first difference, or integrated of order one, I(1). The results of cointegration test showed that the third time series of stock prices, exchange rates, and economic growth are not cointegrated. The results of effect test showed that there is an effect of the stock prices and exchange rates on Indonesia's economic growth. Furthermore, the amount of influence stock prices on economic growth is greater than the effect of exchange rates on economic growth. Keywords: Stock price, Exchange rate, Economic growth, Autoregressive distributed lag (ADL) model JEL Classifications:C44, F310, G120, O047